BIOSURFACTANTS: POSSIBLE ROLES IN ENVIRONMENTAL MANAGEMENT -A REVIEW - Abraham, P.; Chinedu, Ezeh Okechukwu; Banaru, Abubakar Abdulrazaq; Dauda, Wadzani Palnam (FUDMA JOURNAL OF SCIENCES, 2023)
Recent years have seen a rise in interest in biosurfactants, which are surface-active compounds produced by microorganisms that affect surfaces, particularly the surface tension of liquid-vapor interfaces. Due to their ability to emulsify and solubilize hydrophobic compounds as result of their amphipathic nature, biosurfactants are useful in degradation of hydrocarbon and are therefore applicable in oil spill management. Because they are biodegradable, have low toxicity, work well at high or low pH levels, and are more environmentally friendly than their chemical equivalents, biosurfactants have merits over their chemical counterparts. Biosurfactants are adaptable materials with a wide range of uses in the biodegradation and bioremediation of environmental contaminants. In addition, they have uses in pharmaceutical, food, and other industries. The continuous interest in biosurfactants results from these benefits and their vast variety of applications. Hydrophobic pollutants such as hydrocarbons and their derivatives are the major environmental issues due to their poor degradation but the use of biosurfactants can enhance their microbial degradation. When microorganisms try to use substrates like hydrocarbon as a source of carbon, they produce a variety of compounds called biosurfactants that help the diffusion into the cell. This review discusses the roles of these microbial products as veritable tools in environmental management with particular emphasis on the roles of biosurfactants in the sanitation of petroleum pollution and bioremediation of soils contaminated by pesticides.
Keywords: Biosurfactants; biodegradation; bioremediation; environmental management; environmental pollution; microorganisms